Ultrasound alpha angles and hip pain and function in female elite adolescent ballet dancers - Biernacki, J. L.; d`Hemecourt, P. A.; Stracciolini, A.; Owen, M.; Sugimoto, D. (Journal of Dance Medicine & Science, 2020)
Femoroacetabular impingement (FAI) is a common anatomical variant in ballet dancers. Cam morphology (a subtype of FAI) and increased alpha angles have been identified as risk factors for hip pain. Ultrasound has recently been used to measure alpha angles in the diagnosis of cam morphology, but its utility remains understudied. The purpose of this study was to investigate the effect of ultrasound measured alpha angles on hip pain and function scores in elite female adolescent ballet dancers. Te alpha angles of 25 dancers (mean age: 15.9 years) were measured using ultrasound and calculated with ImageJ Software. Cam morphology was defined by alpha angles of 60° or greater. Participants rated their hip pain and function using the International Hip Outcome Tool 12 (iHOT-12) survey. For normally distributed variables, the independent t-test was performed, and for abnormally distributed variables, the Mann-Whitney U Test. Along with mean and standard deviation (SD) values, median score, interquartile range (IQR), and 95% confidence intervals (95% CIs) were also analyzed. Significantly lower iHOT-12 scores were found in dancers with alpha angles = 60° (mean ± SD, 74.34 ± 13.01; 95% CIs, 58.18, 90.50, median 67.20; IQR, 18.55), compared to dancers with alpha angles = 60° (mean ± SD, 80.22 ± 15.65; 95% CIs, 72.90, 87.54; median, 81.60; IQR, 16.35; p = 0.001). It is concluded that: 1. elite female adolescent ballet dancers with alpha angles higher than 60° experienced worse hip pain and function; 2. alpha angles may impact hip pain and function in these dancers; and 3. further studies should use a prospective design to investigate the predictive ability of their findings.